E-learning resources and cognitive expectations in introductory physics - Mistades, Voltaire Mallari (Animo Repository, 2024)
Responding to the challenge of Garrison and Anderson (2003) that educators put "more effort and creativity... into understanding and appreciating the integrating element of teaching presence to facilitate critical thinking and higher-order learning outcomes within an e-learning context", the paper describes the use of e-learning resources - the Integrated Virtual Learning Environment [http://ivle.dlsu.edu.ph], physlets (short for Physics applets/animations), and Internet sites dedicated to Physics students - in the author's Introductory Physics classes during the last two academic years. In this paper, teaching presence is taken in the context of the definition provided by Anderson, et.a l. (2001), 'the design, facilitation, and direction of cognitive and social processes for the purpose of realizing personally meaningful and educationally worthwhile learning outcomes'.Using a survey instrument developed and validated by the University of Maryland Physics Education Research Group (Redish, et.al., 1998, the paper also documents how students' cognitive expectations - their expectations about the learning process and the structure of knowledge - change after going through their Introductory Physics course.